(untitled) (Rivista di Studi e Ricerche sulla criminalità organizzata, 2023)
The film and television story has developed numerous narratives of organized crime, so much so that it has made a decisive contribution to the creation of its imagery. But what tools does a screenwriter have at his disposal when dealing with these issues? How does he manage the relationship between reality and fiction? Or the need to reconcile his desire for civic condemnation with the rules of dramaturgy? The article reconstructs the choices made by the author during her career as a screenwriter from “I cento passi” to “Il nostro generale”.